(untitled) - Teeler, Dede; Dede Teeler and Peta Gray (Harlow, England, 2000)
Packed with practical ideas on how to use the internet with your classes and for your own professional development. Offers a clear introduction to using the internet including browsers, directories and search engines, and to understanding simple Netiquette'. Examines what makes a good internet-based activity, how to adapt materials for use in the classroom, and how to design an internet-based course. Detailed appendices with a clear explanation of technical terms, and a list of websites relevant to teachers
Keywords: English language; Anh ngữ thực hành